2009
DOI: 10.1007/s11104-009-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil organic carbon and total nitrogen after 28 years grassland afforestation: effects of tree species, slope position, and soil order

Abstract: The effect of conversion of grassland to woodland on organic carbon (OC) and total nitrogen (TN) has significance for global change, land resource use and ecosystem management. However, these effects are always variable. Here, we show results of a study in an arid area in China on profile distribution of OC and TN in soils covered by two different woody tree canopies and outer canopy space (grassland between woody plant canopies). The soils were at various slope positions (upper, middle and lower slopes) for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 51 publications
6
38
0
1
Order By: Relevance
“…3 to 5. The decreasing trend in SOC stocks in the 0-to 100-cm layer in the present study was a natural phenomenon and in agreement with previous studies on the CLP (Han et al, 2010;Wei et al, 2010) and at other study sites with different vegetation (Omonode and Vyn, 2006). Little information about SOC below 100 cm is available for comparison.…”
Section: Depth Dependence Of Soil Organic Carbon Stockssupporting
confidence: 92%
“…3 to 5. The decreasing trend in SOC stocks in the 0-to 100-cm layer in the present study was a natural phenomenon and in agreement with previous studies on the CLP (Han et al, 2010;Wei et al, 2010) and at other study sites with different vegetation (Omonode and Vyn, 2006). Little information about SOC below 100 cm is available for comparison.…”
Section: Depth Dependence Of Soil Organic Carbon Stockssupporting
confidence: 92%
“…Pastures with grazing intensity strongly influenced soil organic carbon declines and/or increases after land conversion. If pastures are overgrazed, inputs from aboveground parts are reduced, and soil carbon stocks could have decreased (Murty et al 2002;Wei et al 2010). As expected, the difference is most pronounced in the top soil (0-20 cm) depth than in the lower soil depth (20-40 cm) for both soil organic matter and total nitrogen.…”
Section: Soil Organic Csupporting
confidence: 58%
“…The present results are consistent with the findings of Su and Zhao (2003), who reported higher SOC in stands of C. microphylla shrub than in active sand dunes. Wei et al (2010) compared the distribution of SOC and N in soils under canopies and in outer tree canopies in semi-arid areas and found that dry-climate, low-C soils had a potential for C sequestration after grassland to woodland conversion. Hu et al (2008) documented a significant potential for soil C sequestration with afforestation in Horqin sandy land, and revealed that Mongolian pine plantations in Horqin sandy land have a great potential to sequester C, which agreed with the present research.…”
Section: Soil Organic C and N Concentrationmentioning
confidence: 99%